2019
DOI: 10.1080/21655979.2019.1586055
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel deep-sea Bacillus circulus strain and uniform design for optimization of its anti-aflatoxigenic bioactive metabolites production

Abstract: 2019) Isolation of a novel deep-sea Bacilluscirculus strain and uniform design for optimization of its anti-aflatoxigenic bioactive metabolites production, Bioengineered, 10:1, 13-22, ABSTRACTThe deep-sea bacterium strain FA13 was isolated from the sediment of the South Atlantic Ocean and identified as Bacillus circulans based on 16S ribosomal DNA sequence. Through liquid fermentation with five media, the cell-free supernatant fermented with ISP2 showed the highest inhibition activities against mycelial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The use of live cells and/or spores offers several additional advantages over the use of metabolites, such as the ability to combine multiple mechanisms, like interference in nematode-host recognition, competition for nutrients, promotion of plant growth, and induction of systemic resistance ( Chinheya et al, 2017 ; Engelbrecht et al, 2018 ; Ramírez-Cariño et al, 2020 ). Additionally, endospores are preferred to prepare commercial formulations because they are highly resistant to adverse environmental conditions, making them suitable for long-term storage and convenient for formulating powdered products for agricultural application ( Zhou et al, 2019 ). In this study, the capacity of B. paralicheniformis TB197 to control PPNs was evaluated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The use of live cells and/or spores offers several additional advantages over the use of metabolites, such as the ability to combine multiple mechanisms, like interference in nematode-host recognition, competition for nutrients, promotion of plant growth, and induction of systemic resistance ( Chinheya et al, 2017 ; Engelbrecht et al, 2018 ; Ramírez-Cariño et al, 2020 ). Additionally, endospores are preferred to prepare commercial formulations because they are highly resistant to adverse environmental conditions, making them suitable for long-term storage and convenient for formulating powdered products for agricultural application ( Zhou et al, 2019 ). In this study, the capacity of B. paralicheniformis TB197 to control PPNs was evaluated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation conditions of NSJ105 were optimized using the uniform design method so that the strain NSJ105 could produce the maximum total saponins. The uniform design has the advantage of time and can cover more factors and levels but lacks the superiority of accuracy [ 26 ]. In this study, the concentration of the total saponins measured in the optimal fermentation protocol 105-DP was very close to the predicted value.…”
Section: Discussionmentioning
confidence: 99%
“…It allows researchers to observe variable impacts more accurately and draw precise conclusions. It finds extensive applications in various fields and can improve efficiency and reliability for results [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there might be unknown aflatoxin-control microorganisms in the marine environment, since it has been reported that Emericella venezuelensis , which can produce aflatoxin, originated from the sea [ 39 ]. There has only been one aflatoxin-inhibiting strain from the deep sea reported so far that could inhibit the growth of aflatoxigenic fungi hypha and the generation of AFB 1 [ 40 ]; nevertheless, no strains with AFB 1 degradation properties from the deep sea have been elucidated. In this study, AFB 1 -degrading strain 13 was isolated from the deep sea and identified as Kocuria rosea .…”
Section: Introductionmentioning
confidence: 99%